Pemisahan dan Penentuan Karakter Fraksi Protein ESA Toxoplasma gondii Secara ImmunologikUntuk Pengembangan Diagnosa - Dewi, Lale Budi kusuma; Agrijanti, Agrijanti (Poltekkes Kemenkes Mataram, 2021)
Toxoplasmosis is a zoonotic disease that attacks vertebrates including humans. T gondi infection cause toxoplasmic encephalitis in immunocompromised patients, blindness, abortion, fetal abnormalities and even fetal death or miscarriage. the diagnosis of toxoplasmosis is mainly based on detection of specific antibodies in serum samples using the T gondii antigen protein. various kinds of antigens are explored to be used as bioresptors to detect antibodies against T gondii in the patient's body. the use of ESA protein has advantages in terms of simple preparation. The lacks is the protein contamination by extraparasitic components so that it can reduce the sensitivity and specificity of T gondii antibodies detection. The purpose of this study is to separate or purify antigenic ESA proteins to increase the sensitivity and specificity detection by purifying ESA proteins with gel filtration chromatography. The results obtained 3 fractionation, the protein ESA fractionation is one of fraction that has antigenic properties towards T Gondii. dipstick test with antigen using fraction 3 the results of ESA protein fractionation, 7 samples were positive from 8 positive samples, gave a sensitivity value of 87.5% and 6 samples were negative from 8 negative samples, giving a specificity value of 75%.